Pilot study of a Spanish language measure of financial toxicity in underserved Hispanic cancer patients with low English proficiency - Shi, Julia J.; McGinnis, Gwendolyn J.; Peterson, Susan K.; Taku, Nicolette; Chen, Ying-Shiuan; Yu, Robert K.; Wu, Chi-Fang; Mendoza, Tito R.; Shete, Sanjay S.; Ma, Hilary; Volk, Robert J.; Giordano, Sharon H.; et al. (Frontiers in Psychology, 2023)
Background Financial toxicity (FT) reflects multi-dimensional personal economic hardships borne by cancer patients. It is unknown whether measures of FT—to date derived largely from English-speakers—adequately capture economic experiences and financial hardships of medically underserved low English proficiency US Hispanic cancer patients. We piloted a Spanish language FT instrument in this population. Methods We piloted a Spanish version of the Economic Strain and Resilience in Cancer (ENRICh) FT measure using qualitative cognitive interviews and surveys in un-/under-insured or medically underserved, low English proficiency, Spanish-speaking Hispanics (UN-Spanish, n = 23) receiving ambulatory oncology care at a public healthcare safety net hospital in the Houston metropolitan area. Exploratory analyses compared ENRICh FT scores amongst the UN-Spanish group to: (1) un-/under-insured English-speaking Hispanics (UN-English, n = 23) from the same public facility and (2) insured English-speaking Hispanics (INS-English, n = 31) from an academic comprehensive cancer center. Multivariable logistic models compared the outcome of severe FT (score > 6). Results UN-Spanish Hispanic participants reported high acceptability of the instrument (only 0% responded that the instrument was “very difficult to answer” and 4% that it was “very difficult to understand the questions”; 8% responded that it was “very difficult to remember resources used” and 8% that it was “very difficult to remember the burdens experienced”; and 4% responded that it was “very uncomfortable to respond”). Internal consistency of the FT measure was high (Cronbach’s α = 0.906). In qualitative responses, UN-Spanish Hispanics frequently identified a total lack of credit, savings, or income and food insecurity as aspects contributing to FT. UN-Spanish and UN-English Hispanic patients were younger, had lower education and income, resided in socioeconomically deprived neighborhoods and had more advanced cancer vs. INS-English Hispanics. There was a higher likelihood of severe FT in UN-Spanish (OR = 2.73, 95% CI 0.77–9.70; p = 0.12) and UN-English (OR = 4.13, 95% CI 1.13–15.12; p = 0.03) vs. INS-English Hispanics. A higher likelihood of severely depleted FT coping resources occurred in UN-Spanish (OR = 4.00, 95% CI 1.07–14.92; p = 0.04) and UN-English (OR = 5.73, 95% CI 1.49–22.1; p = 0.01) vs. INS-English. The likelihood of FT did not differ between UN-Spanish and UN-English in both models (p = 0.59 and p = 0.62 respectively). Conclusion In medically underserved, uninsured Hispanic patients with cancer, comprehensive Spanish-language FT assessment in low English proficiency participants was feasible, acceptable, and internally consistent. Future studies employing tailored FT assessment and intervention should encompass the key privations and hardships in this population.